A new iphiculid crab (Crustacea, Brachyura, Leucosioidea) from the Middle Miocene of Austria, with notes on palaeobiogeography of Iphiculus - Hyžný, Matúš; Gross, Martin (Zootaxa, 2016)
A new fossil species of the iphiculid genus Iphiculus Adams & White, 1849, (Crustacea, Brachyura) is described on the basis of three specimens from the Middle Miocene Florian Beds of Styria, Austria. Iphiculus eliasi sp. nov. constitutes the first European record of the genus. This occurrence represents the oldest record of Iphiculus, having implications for the palaeobiogeographic history of the family Iphiculidae. It is suggested that Iphiculus may have originated in the Western Tethys and migrated subsequently into the Indo-West Pacific. Alternatively, its current geographic restriction to the Indo-West Pacific can be a remnant of an ancient broader geographic distribution.